The role and scope of architectural and conservation research procedures in the process of restoring the splendour of an architectural monument created after 1945 on the example of the Suburban Railway Station in Gdynia - Orchowska-Smolińska, Anna; Kriegseisen, Anna (Rola i zakres architektoniczno-konserwatorskich procedur badawczych w procesie przywracania świetności zabytku architektury powstałej po 1945 r. na przykładzie Dworca Podmiejskiego w Gdyni, 2022)
Modern Movement buildings, despite their relatively recent construction, are sometimes affected by radical transformations of layout and form. The railway stations being one of the most important public buildings in the city are a special group of them. Due to long-term and intensive use they may bear the signs of exploitation of parts of its substance and have secondary transformations disharmony with the building. The subject of the article are architectural and conservation studies of the Suburban Railway Station in Gdynia, built in the mid-1950s. The authors of the article set themselves the goal of presenting the research procedures developed for it in the years 2016–2022, which are an introduction to revaluation process. The research methods used during the field work made it possible to identify the originally used techniques of execution and finishing methods and to determine the procedures for their reconstruction using conservation methods. The results of the conducted research became the basis for determining the scope of conservation protection of the station building, as well as the possibility of interfering with its partly “functionless” substance through adaptation and modernization activities.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 117-128
Keywords: architektura; architectural and conservation documentation; program of conservation and restoration works; architecture after 1945; revalorization; Gdynia Suburban Railway Station; dokumentacja architektoniczno-konserwatorska; program prac konserwatorskich i restauratorskich; architektura po 1945; rewaloryzacja; Dworzec Podmiejski w Gdyni